Método de monitoramento para gestão de portfólio de produtos - Herzer, Rafael (Universidade do Vale do Rio dos Sinos, 2016)
Product Portfolio Management is attracting the interest of the managers of the corporations. With the competitiveness of the market, it is difficult to find an organization that does not have a portfolio of products to manage. The Portfolio Management deals with resource allocation decisions and how will the portfolio of current products be compouse, being an extremely important tool for the result, especially financial, for the organizations. This process of management and decision making is considered complex to company managers, since the portfolio needs to be periodically revised, always seeking to maximize value and correct balance of products on the market. There are several methods in the literature to perform portfolio management, among which financial models, financial probabilistic models, scores and checklists models, analytical hierarchy of approaches, behavioral approaches and approaches map or diagram bubbles are the most relevant. While there are several methods in the literature to make the portfolio management, there is no consensus about which method should be used in each specific step. These methods also require the intervention of managers, taking into account that generally available information for decision-making are not complete or accurate. This paper aims to propose a method, which, through a multi-criteria system containing an econometric model, identifies changes in the economic environment and business indicators and then, from the profile monitoring, can set the exacly time for change portfolio of products. We performed the Monte Carlo simulation study to assess the sensitivity of the various parts that make up the method. The results showed false alarm rate and mean time to detect changes similar to previous studies. Finally, the application of the model is illustrated by a real case using data provided by a multinational company, agricultural segment.
Keywords: Gestão de portfólio de produtos; Monitoramento de resíduos; Modelo de regressão multivariada; Detecção de mudanças; Ferramentas estatísticas; Product portfolio management; Profile monitoring; Multivariate regression model; Detecting changes; Multicriteria method; ACCNPQ::Engenharias::Engenharia de Produção